Nutritional and sensory properties: snack food made from high-quality cassava flour and legume blend - Maziya-Dixon, B.B.; Alamu, Emmanuel Oladeji; Popoola, I.O.; Yomeni, M. (Wiley, 2017)
The nutritional benefits of grain legumes such as cowpea and soybean in sub-Saharan Africa have not been fully utilized to alleviate problem of protein-malnutrition in this region. This study aimed to evaluate and compare the nutritional properties and sensory evaluation of snack food made from high-quality cassava flour (HQCF) and soybeans (50:50), and HQCF and cowpea (50:50). Sensory evaluation was conducted among panellists in Nigeria and DR Congo. Results showed that the soy variant of the snack contained significantly higher protein than the cowpea variant. There was cross-cultural difference in snack preference between panellists in Nigeria and DR Congo. Panellists in DR Congo preferred the aroma of the unboiled soy variant, whereas panellists in Nigeria preferred the boiled soy variant more. This study showed the potential of legumes and cassava in the snack food sector not only as a partial substitute for wheat flour but as a major ingredient and also form basis for the new product development in the snacks food industry. The developed product could be possibly used to alleviate the protein-malnutrition among the vulnerable groups of most developing countries.